Review of Regulatory Requirements for Implementing an Aging Management System for the IPR-R1 Triga Reactor of CDTN - ANA ROSA BALIZA; AMIR ZACARIAS MESQUITA; youssef morghi (Brazilian Journal of Radiation Sciences)
CDTN (Centro de Desenvolvimento da Tecnologia Nuclear) owns an IPR-R1 Triga research reactor (Training, Research, Isotopes, General Atomics) that has been in operation for over 60 years. One of the issues that comes up by this operating time is aging management. Aging management includes the functions and issues involved with management, maintenance, operation, inspections, operational testing, design changes, structural calculations, and others. Management of aging of structure, system and equipment must be implemented proactively throughout the life of a research reactor. According to the CNEN standard NE 1.04, in the absence of national standards, the documents of the International Atomic Energy Agency (IAEA) or the country that is the designer must be used. The use of the IAEA standards is beneficial for many reasons, including the global base and years of experience and the variety of documents related to the aging management of nuclear research reactors. However, this reactor is an American project, so the requirements of Nuclear Regulatory Commission (NRC) are also applicable. This article will discuss the IAEA and NRC requirements to implement an aging management system for the CDTN IPR-R1 Triga Reactor.